Pendampingan Pencatatan Laporan Keuangan pada Usaha Kecil Menengah Sektor Retail Toko MESMart di Palangka Raya - Hilmi Satria Himawan; Sofyan Hakim; Verra Rizki Amelia; Ria Muliyana; Fitriani Fitriani; Leni Wulan Dari (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
MSMEs play an important role in the global economy, driving job creation, innovation, and economic growth. However, there are challenges such as financing and regulatory burdens caused by, among other things, difficulties in preparing financial reports. These obstacles begin with several issues, namely the loss of invoices, which makes it difficult to gather data for financial report preparation, discrepancies in stock between the cashier application and physical counts, and ineffective stock opname. Based on these issues, the objective of this Community Service is to provide an overview of ideas for optimizing the work system at MSME MESMart and to assist in the preparation of financial reports easily using a cloud-based accounting application called Jurnal Bijak. With the implementation of community service, it is hoped that various problems arising from obstacles in financial report preparation can be minimized. The method used is Participatory Action Research (PAR), involving active participation from participants to identify problems and seek solutions collaboratively. The results of this activity can implement work programs, from optimizing store program, creating cloud-based financial reports, and arranging store displays.